2022
DOI: 10.1093/braincomms/fcad009
|View full text |Cite
|
Sign up to set email alerts
|

Altered temporal connectivity and reduced meta-state dynamism in adolescents born very preterm

Abstract: Adolescents born very preterm have an increased risk for anxiety, social difficulties, and inattentiveness, i.e., the “preterm behavioral phenotype”. The extreme end of these traits comprises the core diagnostic features of attention and hyperactivity disorders and autism spectrum disorder, which have been reported to show aberrant dynamic resting state functional network connectivity. This study aimed to compare this dynamism between adolescents born very preterm and controls. A resting state f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Studies in neuropsychiatric disorders with cognitive impairments have shown conflicting results on dynamic functional connectivity, with some studies showing decreased values for all global brain dynamic indices in schizophrenia, 24 autism, 52 some forms of major neurocognitive disorder 26 and in preterm born adolescents, 53 and others showing higher values for these metrics, including Alzheimer's disease 54 and other neonatal disorders such as foetal alcohol spectrum disorder. 55 Consistent with these studies, we found a subtle cognitive impairment indicated by inattention, hyperactivity and impulsivity scales in subjects at risk for CUD.…”
Section: Meta-state Changes In the Risk Of Cudmentioning
confidence: 99%
“…Studies in neuropsychiatric disorders with cognitive impairments have shown conflicting results on dynamic functional connectivity, with some studies showing decreased values for all global brain dynamic indices in schizophrenia, 24 autism, 52 some forms of major neurocognitive disorder 26 and in preterm born adolescents, 53 and others showing higher values for these metrics, including Alzheimer's disease 54 and other neonatal disorders such as foetal alcohol spectrum disorder. 55 Consistent with these studies, we found a subtle cognitive impairment indicated by inattention, hyperactivity and impulsivity scales in subjects at risk for CUD.…”
Section: Meta-state Changes In the Risk Of Cudmentioning
confidence: 99%